Konsep Kemanfaatan Religius dalam Redaksi Awal Akta Pembiayaan Murabahah (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the application of the legal principle of utility (kemanfaatan hukum) in relation to the inclusion of the phrase Basmallah at the beginning of authentic deeds in Murabahah financing contracts. In notarial practice, it has been found that certain notaries include the phrase “Bismillahirrahmanirrahim” at the beginning of the redaction of Islamic financing deeds. However, the form and structure of authentic deeds are explicitly regulated in Article 38 of the Notary Act (UUJN), which serves as the normative reference for notaries in drafting legally binding deeds. According to Article 1868 of the Indonesian Civil Code (KUHPerdata), an authentic deed is a document drafted in a format prescribed by law, created by or before a public official authorized for such matters, and executed at a place designated by law. Therefore, the inclusion of the Basmallah, which is not stipulated in the formal structure of deeds, may pose legal issues as it can be deemed a deviation from formal requirements, potentially undermining the evidentiary strength of the deed. To ensure both the utility and legal certainty of authentic deeds, it is necessary to reaffirm the formal boundaries as outlined in Article 1869 of the Civil Code, so that deeds drawn up by notaries maintain both formal and substantive legal validity. The scope of this study encompasses three main aspects: First, whether the inclusion of the Basmallah at the beginning of a Murabahah financing deed holds legal authenticity; second, to what extent such inclusion aligns with the principle of legal utility.